2013
DOI: 10.1021/la4009174
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptoid Brushes by Surface-Initiated Polymerization of N-Substituted Glycine N-Carboxyanhydrides

Abstract: Polypeptoid brushes were synthesized by surface-initiated polymerization of N-substituted glycine N-carboxyanhydrides (NNCAs) on self assembled amine monolayers. Using the presented grafting from approach, polypeptoid brush thicknesses of approx. 40 nm could be obtained as compared previously reported brush thicknesses of 4 nm. Moreover, hydrophilic, hydrophobic and amphiphilic polymer brushes were realized which are expected to have valuable applic-tions as non-fouling surfaces and as model or references syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 49 publications
(110 reference statements)
3
50
0
Order By: Relevance
“…Zhang and co-workers conducted N-heterocyclic carbene-mediated living polymerization of N-substituted glycine NCAs, which produced cyclic PSar-b-PNBG block copolymers with quantitative yields and low PDIs. 66 In this work, we prepared P(Sar-r-NBG) random copolymers through the primary-amine initiated polymerization of N-substituted glycine NTAs. 65 The polymers self-assembled in aqueous solution, and were used as emulsifiers, micelles, or polymersomes with a hydrophilic corona and a hydrophobic core or membrane.…”
Section: Synthesis and Characterization Of P(sar-r-nbg)mentioning
confidence: 99%
“…Zhang and co-workers conducted N-heterocyclic carbene-mediated living polymerization of N-substituted glycine NCAs, which produced cyclic PSar-b-PNBG block copolymers with quantitative yields and low PDIs. 66 In this work, we prepared P(Sar-r-NBG) random copolymers through the primary-amine initiated polymerization of N-substituted glycine NTAs. 65 The polymers self-assembled in aqueous solution, and were used as emulsifiers, micelles, or polymersomes with a hydrophilic corona and a hydrophobic core or membrane.…”
Section: Synthesis and Characterization Of P(sar-r-nbg)mentioning
confidence: 99%
“…[58] The surface-confined polymerization of Me-NCAs and Bu-NCAs using a surface-tethered primary amine initiator has also been investigated by Luxenhofer and Jordan et al to produce hydrophilic, hydrophobic, or amphiphilic polypeptoid homopolymer or block copolymer brushes. [59] Polypeptoid thin films up to 40 nm can be produced by this method. Surface-confined growth of polypeptoid brushes in conjunction with micro-patterning has also enabled access to micro-patterned polypeptoid thin films.…”
Section: Synthesis Of Linear Polypeptoidsmentioning
confidence: 99%
“…However, the need for purification after each step, and the possible detrimental influence of the surface on chemical reactions could be problematic. Recently, surface-initiated polymerization (SIP) reactions (Islam et al 2014; Lei et al 2014; Wang et al 2011) have been demonstrated to occur on various forms of solid substrates (bulk surface, powders, and nanoparticles) composed of gold (Yenice et al 2015), silica (Prucker and Ruhe 1998a; Prucker and Ruhe 1998b; Schneider et al 2013), or fumed silica (Hou et al 2010). …”
Section: Introductionmentioning
confidence: 99%